Forest Growth Responses to the Pollution Climate of the 21st Century 1999
DOI: 10.1007/978-94-017-1578-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Forest Health in North America: Some Perspectives on Actual and Potential Roles of Climate and Air Pollution

Abstract: Abstract. The perceived health of forest ecvqems over large temporal and spatial scalm can be strengly inlluenced by the frames of refmence chosen to e+aluate both forest condition and the timctional integrity of sustaining forsl processes. North American forests arc diverse in range, species compceiti~ past disturbance history, and current managementpracticcs.~~eforcthcimplikltionsofchangesinenvLonmentalstessGan~h~cpollution~or global climate change on health ofthese for&s will vary widely acrom the la&cape. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 162 publications
0
53
2
Order By: Relevance
“…We also did not find any evidence of collateral damage to balsam fir or paper birch in the wake of widespread spruce mortality (Perkins et al 1992;McLaughlin and Percy 1999). However, there were important changes in the rate and nature of biomass accumulation since the mid-1980s.…”
Section: Forestwide Implications Of Spruce Declinementioning
confidence: 59%
“…We also did not find any evidence of collateral damage to balsam fir or paper birch in the wake of widespread spruce mortality (Perkins et al 1992;McLaughlin and Percy 1999). However, there were important changes in the rate and nature of biomass accumulation since the mid-1980s.…”
Section: Forestwide Implications Of Spruce Declinementioning
confidence: 59%
“…In a comprehensive retrospective review of the roles of air pollutants and climate in North American forest health, McLaughlin and Percy (1999) reported that O 3 was deleteriously affecting forest ecosystem function across large and geographically widely separated areas of the continent. When considering relevance of this current research within the ambient exposure-based metric context (Foley et al, 2003), it is important to note that the growing season 4th highest daily max.…”
Section: Discussionmentioning
confidence: 99%
“…Since the late 1950s, an extensive scientific literature has been built on the O 3 impacts on forest trees (see reviews by Kickert and Krupa, 1990;Chappelka and Samuelson, 1998;McLaughlin and Percy, 1999;Percy, 2002;Percy et al, 2003;Andersen, 2003;Ashmore, 2004;Karnosky et al, in press), forest ecosystems (Miller and McBride, 1999;Bytnerowicz et al, 2003) and physiologically based modeling of North American forest response. Ollinger et al (1997) simulated the effects of O 3 on hardwood forest types in the northeastern US and estimated growth reductions between 3% and 22%.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced carbon fixation during non-stressed periods, driven by the fertilization effect of elevated CO 2 , may compensate for reduced availability of soil moisture (Hanson and Weltzin 2000). However, changes in ambient levels of ozone and/or acidic deposition can alter basic processes of water, carbon, and nutrient allocation by trees (McLaughlin and Percy 1999). Increased nitrogen levels in the atmosphere may also promote plant growth, but could potentially pollute water resources (Johnson et al 2000).…”
Section: Ecosystemsmentioning
confidence: 99%